Pengaruh Kredibilitas Celebrity Endorsement, Promosi, dan Kepercayaan terhadap Keputusan Pembelian Produk Khayr Scarf (Studi Kasus Mahasiswa FEB UNISMA) - Assagaf, Nurul Syifa; Hidayati, Nur; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of celebrity endorsement credibility, promotion, and trust on purchasing decisions for khayr scarf products (Case Study of Unisma FEB Students). The sampling technique used purposive sampling to obtain a sample of 70 respondents. The data collection method used a questionnaire. The data analysis technique used in this research is multiple linear regression. The results showed that simultaneously celebrity endorsement credibility, promotion, and trust have a positive and significant effect on purchasing decisions. Likewise, partially celebrity endorsement credibility, promotion, and trust have a positive and significant effect on purchasing decisions. Keywords: celebrity endorsement credibility, promotion, trust, purchasing decisions.